Effects of legal and unauthorized immigration on the US social security system - Selçuk Eren; Hugo Benítez-Silva; Eva Cárceles-Poveda (Levy Economics Institute of Bard College, 2011)
Immigration is having an increasingly important effect on the social insurance system in the United States. On the one hand, eligible legal immigrants have the right to eventually receive pension benefits but also rely on other aspects of the social insurance system such as health care, disability, unemployment insurance, and welfare programs, while most of their savings have direct positive effects on the domestic economy. On the other hand, most undocumented immigrants contribute to the system through taxed wages but are not eligible for these programs unless they attain legal status, and a large proportion of their savings translates into remittances that have no direct effects on the domestic economy. Moreover, a significant percentage of immigrants migrate back to their countries of origin after a relatively short period of time, and their savings while in the United States are predominantly in the form of remittances. Therefore, any analysis that tries to understand the impact of immigrant workers on the overall system has to take into account the decisions and events these individuals face throughout their lives, as well as the use of the government programs they are entitled to. We propose a life-cycle Overlapping Generations (OLG) model in a general equilibrium framework of legal and undocumented immigrants' decisions regarding consumption, savings, labor supply, and program participation to analyze their role in the financial sustainability of the system. Our analysis of the effects of potential policy changes, such as giving some undocumented immigrants legal status, shows increases in capital stock, output, consumption, labor productivity, and overall welfare. The effects are relatively small in percentage terms but considerable given the size of our economy.
Keywords: J14; J26; J65; 330; legal and undocumented immigration; social security; remittances; life-cycle models; OLG models; general equilibrium models